Transforming Human Resources Recruitment: The Impact of Artificial Intelligence (AI) on Organizational Attractiveness and Applicant Intent - Mirzam Arqy Ahmadi; Rahma Ayuningtyas Fachrunisa; Ahmad Baihaqi Esaputra; Fidaus Kurniawan; M. Ilham Timur Abdillah (Benefit: Jurnal Manajemen dan Bisnis, 2024)
In today's rapidly evolving technology landscape, this proposal investigates the transformative field of human capital recruiting through the integration of Artificial Intelligence (AI) and its impact on organizational attractiveness and applicant intent. This research aims to explore prospective employees' perceptions of AI-based recruitment processes and their impact on organizational attractiveness, as well as their intentions to apply for job opportunities. A quantitative research approach was used using an online questionnaire distributed via Google Forms, qualitative methods were also applied in this research to add variation to the research. The interview process and distribution of this questionnaire is to measure the attractiveness of the organization's brand in five dimensions, applicant intentions through five specific items, and AI recruitment through five additional items. Data analysis was carried out using Structural Equation Modeling (SEM) to examine factors and test hypotheses. This questionnaire was distributed via social media platforms, using a Likert scale to capture different responses. Leveraging a diverse body of literature on AI in recruiting and organizational brand appeal, this research provides a comprehensive examination of the modern recruiting landscape. Through methodological rigor and strategic use of technology, this research aims to explain the dynamic interactions between AI, organizational attractiveness, and applicant intent, thereby contributing valuable insights to the growing field of HR management. Apart from that, in an effort to support the Independent Campus Learning program promoted by the government, this research will be carried out by a research team consisting of four lecturers and four students.